"Glocalization" of Health Information: Considering Design Factors for Mobile Technologies in Malaysia. (April 2020) - Saru, Evelyn H.; Wojahn, Patti
Mobile phones offer promising solutions to basic health-care provisions for developing countries like Malaysia. However, for such technologies to be useful for health and medical intervention, information designers must make information shared via small-screen usable for diverse cultural audiences within a nation. In this entry, we use the international patient experience design framework to propose a heuristic for addressing this situation. This approach can provide insights that can facilitate the "glocalization"—or creating materials to address specific cultural contexts and make health and medical information more usable to diverse populations living in the same country.